Classification and determination of the tobacco raw materials authenticity during the forensic examination - S. A. Trofimets (Bulletin of Kharkiv National University of Internal Affairs)
The scientific article examines the peculiarities of classification (botanical, geographical, commodity, international); requirements for the quality of tobacco raw materials and their safety for human health and life, as well as requirements for packaging and labelling in order to improve the examination of tobacco raw materials. Methodological recommendations for determining the authenticity of tobacco raw materials have been developed, which can be used in practical work by customs officers when conducting an examination of goods of group 24 of the Ukrainian Classifier of Goods for Foreign Economic Activity. The identification tasks of the commodity expertise of tobacco raw materials (identification of the type of tobacco, establishment of the grade, quality control, determination of the degree of processing, analysis of aroma and taste) are defined. Modern methods of analysis are presented, in particular, instrumental methods used to establish quality and safety indicators (visual inspection, microscopic analysis, chemical analysis, physicochemical methods, gas chromatography and mass spectrometry, spectral analysis). These methods allow to examine tobacco raw materials at the molecular, chemical and morphological levels to obtain objective information about its quality, safety and other characteristics that may be important in litigation. The article provides a systematisation of information on the characteristic defects of tobacco raw materials, namely: mould, rot, drying, cracking, deformation (these defects may arise as a result of various factors, such as climatic conditions, methods of growing, storing and processing of tobacco raw materials). Defects that are characteristic of low-quality products with signs of spoilage: impurities and contamination, mould, rot, drying out, cracking. The mechanism for conducting a forensic examination of tobacco raw materials with the aim of objective assessment of quality, safety and other characteristics is described.